Empowerment of Haranggaol Subdistrict community, Haranggaol Horison District, Simalungun Regency, North Sumatra in efforts to improve local wisdom - Ritonga, Fajar Utama; Siagian, Matias; Masmur, Indra (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The Collaborative Work Lecture with BKS West PTN is one of the community service programs conducted by 20 state universities where the University of North Sumatra is the host of the program. In the KKN program, we realize one of the tri dharma of higher education namely community empowerment. The aim of this program is that students are expected to gain learning experience through involvement in the community who directly find, formulate, solve and overcome problems that are in the field. The Community Service Program that we carry out is devoted to the community in Haranggaol Village, Haraggaol Horison District, Simalungun Regency, North Sumatra Province with the program "Community Empowerment of the Haranggaol Village, Haranggaol Horison District, Simalungun Regency, North Sumatra Province in an Effort to Improve Local Wisdom and Ecotourism in the Region of North Sumatra. This program is expected to be able to contribute to the community in the form of helping improve basic facilities and infrastructure as well as increasing the human resources available in the Haranggaol Basin so that local wisdom and ecotourism are of higher quality and help local communities maintain natural resources so that they are sustainable